Military Campaigns of Modibo Buba Yero and the Emergence of Gombe Emirate, 1804 –1902: A Study in Sokoto Jihad - Japhet Audu, Bem; Jimoh Audu, Sedenu; Ibrahim, S. (Kashere Journal of Humanities, Management and Social Sciences, 2022)
One event in the pre-colonial history of Nigeria that has received much attention from scholars is obviously the 19th Century Jihad and the creation of the Gombe emirate. Quite a lot have written on various aspects of the issue. Such areas include the evolution of the emirate, the administrative system as well as the effect of the Jihad in the Gongola basin and the Benue valley region. Despite this development, not much has been done in the military history of Gombe. Though a number of works exist on the role of Buba Yero in the Jihad and subsequent creation of the Gombe emirate, such was not done in the military context of the Jihad and certainly did not bring out the strategies and tactics adopted in the battles fought in the Jihad. Consequently, the choice of this topic was motivated by the desire to fill the identified lacuna in the military history of the Gombe and an attempt to reexamine the military campaigns of Buba Yero and how the activities brought about the emergence of Gombe emirate. The study made use of primary and secondary sources and adopted the methodological approach that involved the narrative and analytical.